PENGARUH NAUNGAN DAN LAMA PENYIMPANAN STEK PADA PERTUMBUHAN JARAK PAGAR (Jatropha curcas L.) DAN JARAK MERAH (Jatropha gossypiifolia L.) - Wawo, Albertus Husein (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2010)
There are two species of Jatropha in East Nusa Tenggara (NTT), i.e. physic nut (Jatropha curcas L.) and red jatropha or cotton leaved physic nut (1. gossypilfolia L). Both species possess potency as traditional medicine. Propagating jatropha by seeds could not be conducted throughout the year because the seeds were produced on certain time only. On dry season in 2005, a research had conducted in Teun Village, Belu Regency, NTT for studying the effect of shading and cutting storage on the growth of the two jatropha species. This research had 12 treatments with two replications and employed Factorial Experimental Design. The data were processed by SAS (Statistic Analysis System) program. The result of this research showed that the growth of physic nut better than that of red jatropha. Light shading stimulated the growth of buds, leaves and roots of cutting of jatropha on 60 days after planting. No significant was found in the growth of buds, leaves and roots of cutting of jatropha that were directly planted and stored for four days. Cutting of both species that stored for four days and placed under light shading (with 70% of light intensity) produced higher bud growth and root length than those placed under dense shading (with 30% of light intensity).